(untitled) (Research, Society and Development, 2021)
Accidents at work are linked to the diversification of productive processes and to the production profile, so research on the subject must consider the specificities of the activities involved. Despite the growing number of studies on the topic, there is still a lack of studies that specifically evaluate the agribusiness sector, therefore, this study aimed to analyze occupational accidents in the input, primary and agroindustrial agribusiness segments, reported in Paraná from 2012 to 2017. An epidemiological, descriptive and quantitative study was developed, based on the Communications of Work Accidents (CAT), registered with the National Institute of Social Security (INSS). There were 51,071 CAT related to agribusiness in the state, the incidence rate was 72.73 accidents per thousand workers. In the period studied, there was a decrease in the number of CAT in all the segments analyzed. The work accidents in the slaughtering of pigs, poultry and other small animals stood out, there were 12,923 CAT registered. The most vulnerable occupation was that of production line feeder, with 10,230 accidents. The most affected body part was the fingers 15,907 (31.15%), and, among the causative agents, knives and fables were among the main ones, causing 4,782 (9.36%) injuries. This study reinforces the importance of the analysis of work accidents in the agribusiness of Paraná, so that it is expected to contribute with evidence to help prevent these injuries in the analyzed segments.